The Meaning of Resilience Among College Students Experiencing Academic Burnout: A Phenomenological Study in Makassar - Husniyah Aisyah Burhan; Anisa Fitriani (Eduvest - Journal of Universal Studies, 2026)
The phenomenon of academic burnout among university students has increased due to high academic demands and pressures within higher education environments. This research aims to explore and understand the meaning of resilience among students experiencing academic burnout in Makassar City. This study employed a qualitative approach with a phenomenological design to capture students’ subjective experiences. Data were collected through in-depth interviews, observation, and documentation using triangulation techniques. The findings reveal that academic burnout is perceived as emotional exhaustion characterized by decreased motivation, cynicism, and psychological distress. The main contributing factors include excessive academic workload, time pressure, and high social expectations. Students’ adaptation processes occur through coping strategies, social support, and phases of falling, reflection, and recovery. The study concludes that resilience is a dynamic process involving the interaction of internal and external factors in developing the ability to survive and grow. These findings imply that universities need to develop targeted intervention programs, including resilience training, peer support systems, and accessible mental health services, while also encouraging educators to adopt more flexible and student-centered academic approaches to prevent and mitigate academic burnout.